Correlation of Parity and Maternal Age with the Incidence of Anemia in Pregnant Women - Anggraeny, Anisa; Risanti, Erika Diana; Agustina, Tri; Lestari, Nining (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Anemia during pregnancy is a public health problem, particularly in developing countries. Women during pregnancy are more likely to have anemia since many women go through their pregnancy without attaining the minimum required intake of iron. The age of the mother and high parity are linked to the psychological and biological elements of pregnant women. This study aims to determine the correlation between parity and maternal age with the incidence of anemia in pregnant women. This study, conducted in Dr Murjani Sampit Hospital, used a cross-sectional design. There were 90 pregnant women involved in this study selected using a purposive sampling method. 58.9% of the participants were primigravid, 56.7% were high-risk age (age 20 years old and age 35 years old), and 54.4 % were anemic. The Chi-square test showed no relationship between parity and anemia in pregnant women (p 0.713); however, there was a significant relationship between age and anemia in pregnant women (p 0.001). The pregnant women with high-risk age had suffered anemia during their pregnancy.